The Associations between Maternal Education, Chronic Energy Deficit, and Anemia in Pregnant Women: An Evidence from Lhokseumawe, Indonesia - Helliyana, Helliyana; Aritonang, Evawany Y.; Sanusi, Sri Rahayu (Journal of Maternal and Child Health, 2019)
Background: Chronic Energy Deficiency (CED) and anemia in pregnant women have a health impact on the mother and child in the womb. This condition can increase the risk of babies with low birth weight, miscarriage, premature birth, even death in mothers and newborns. This study aims to determine the relationship between CED and anemia in pregnant women at the Muara I Health Center in Lhokseumawe City in 2017.Subjects and Method: This study was a cross-sectional study conducted at the Muara I Community Health Center, Lhokseumawe, in December 2017. A sample of 90 pregnant women was selected by consecutive sampling. The dependent variable was the anemia of pregnant women. The independent variables were education and CED. CED was measured based on maternal mid-upper arm circumference (MUAC) during pregnancy using MUAC tape. The hemoglobin level was measured by Hb Sahli. Other data were measured using a questionnaire. The data were analyzed using multiple logistic regression tests.Results: CED has a significant positive and statistically significant effect on anemia in pregnant women (OR = 64.34; 95% CI = 15.10 to 274.10; p <0.001). Low maternal education has a positive effect but was statistically significant towards anemia in pregnant women (OR = 3.15; 95% CI = 0.81 to 12.27; p = 0.099).Conclusion: CED and low maternal education have a positive effect on anemia in pregnant women.Keywords: anemia, pregnant women, education, chronic lack of energyCorrespondence: Helliyana, Masters Program in Public Health, Faculty of Public Health, Universitas Sumatera Utara, Jl. Prof. T. Maas, Medan, Sumatera Utara. Email: andybaso11@gmail.com. Mobile: 085260129999.Journal of Maternal and Child Health (2019), 4(5): 312-316https://doi.org/10.26911/thejmch.2019.04.05.02